1999
DOI: 10.1094/cchem.1999.76.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rough Rice Drying and Storage Conditions on Sensory Profiles of Cooked Rice

Abstract: In both domestic and international markets, the end‐use quality of rice affects its market value and acceptability to consumers. The effect of various postharvest processing treatments on sensory characteristics of cooked rice was investigated using sensory descriptive methods. Cooked rice quality was affected (P < 0.05) by rough rice wet holding, drying temperature, storage temperature, and storage duration. Cohesiveness of mass and hardness of sample were significantly affected by the temperature of drying. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 8 publications
3
38
0
Order By: Relevance
“…Vacuum packed seeds recorded higher score for taste compared to polythene bags, while lower score for gunny bags and cloth bags. Enhanced storage period increases the taste which is more acceptable than fresh rice (Meuellenet et al, 1999). In the present investigation aroma, flavour and colour for cooked rice decreased with advancement in storage period.…”
Section: Interaction Mean (S X C)supporting
confidence: 43%
“…Vacuum packed seeds recorded higher score for taste compared to polythene bags, while lower score for gunny bags and cloth bags. Enhanced storage period increases the taste which is more acceptable than fresh rice (Meuellenet et al, 1999). In the present investigation aroma, flavour and colour for cooked rice decreased with advancement in storage period.…”
Section: Interaction Mean (S X C)supporting
confidence: 43%
“…Therefore, factors affecting such measures are of great importance and thus studied extensively. These factors include planting and pre-harvest treatments, harvest moisture content, drying, storage and milling (Afzalinia et al 2004;Champagne et al 2004;Daniels et al 1998;Daniels et al 1996;Meullenet et al 1999;Pearce et al 2001;Ranalli et al 2003;Saleh and Meullenet 2007;Wang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Drying temperature of rice, for instance, was reported to significantly affect rice functionality. Meullenet et al (1999) reported that drying rice at high temperature (54.3°C) produced less firm cooked rice kernels, but with higher cohesiveness of mass. During milling, however, the temperature of milled rice usually rises in a high order of magnitude but is of short duration, known as flash temperature (Guha and Chowdhury 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The technique has been used extensively for determining the effect of different growing and/or processing conditions on sensory properties of rice (Champagne et al 1997(Champagne et al , 2004a(Champagne et al , b, 2007(Champagne et al , 2009Meullenet et al 1999Meullenet et al , 2000.…”
Section: Introductionmentioning
confidence: 99%